Pengaruh Kecerdasan Intelektual (IQ), Kecerdasan Emosional (EQ), Dan Kecerdasan Spiritual (SQ) Dalam Menentukan Risiko Kecurangan - Joko Pramono; Maria Entina Puspita (ECONBANK: Journal of Economics and Banking, 2020)
This research aims to test empirically the influence of intelligence quotient (IQ), emotional intelligence (EQ) and spiritual intelligence (SQ) on audit judgment in determining the risk of fraud. The objects of this research were the Public Accounting Firms in Jakarta. The data collection techniques used was purposive sampling method with online questionnaire instrument. In this study, the respondents were 40 auditors. The data were analyzed using multiple regression analysis method. This research showed that intelligence quotient (IQ) affected the audit judgment in determining the risk of fraud, while emotional intelligence (EQ) and spiritual intelligence (SQ) did not have an influence on the ability of audit judgment to determine the risk of fraud